INCREASING AWARENESS OF DEPRESSION IN ADOLESCENTS AND CHILDREN THROUGH ONLINE CAMPAIGN ACTIVITIES - Aloysia Ayfen Senjaya; Vivia Inayah Hadi; Hasna Rosyada Fajrin; Wahyu Nur Latifah; Cempaka Puspa Kencana; Asri Adiningtyas; Tiara Diah Sosialita; Nur Ainy Fardana Nawangsari (Universitas Airlangga, 2023)
Cases of depression in children and adolescents show high rates in Indonesia. According to Riskesdas (2018) adolescents (15–24 years) in Indonesia have a percentage of depression around 6.2% and according to the Yogyakarta branch of Ikatan Dokter Anak Indonesia or Indonesian pediatrician association revealed that 3% of school-aged children and 6% of adolescents experience major depressive disorder. This sizable number comes from the assumption of the public that depression does not occur in children and adolescents. Therefore, the provision of information that increases public knowledge about depression in children and adolescents must be carried out so that both early and curative interventions can be carried out so that in the long run, the prevalence of depression in children and adolescents is reduced. This effort uses two methods 1) disseminating information through Instagram content @semicolonial.id, and 2) digital campaigns via Instagram of each campaign participant. The increase in knowledge of campaign participants (N = 21, Range age = 14–50 years, Mage = 23.5) was measured using pre-test and post-test. The data processing used a descriptive statistical data analysis through SPSS version 25. The results shows an increase in participants' knowledge before (Range = 40–100, Mean = 71.9) and after (Range = 60–110, Mean = 91.9) the campaign. In conclusion, this campaign was successful in increasing the knowledge of campaign participants about depression in children and adolescents.